2014
DOI: 10.1037/a0036200
|View full text |Cite
|
Sign up to set email alerts
|

Working together to solve disparities: Latina/o parents’ contributions to the adaptation of a preventive intervention for childhood conduct problems.

Abstract: Left untreated, conduct problems can have significant and long-lasting negative effects on children’s development. Despite the existence of many effective interventions, U.S. Latina/o children are less likely to access or receive evidence-based services. Seeking to build the foundation to address these service disparities, the current study used a Community-Based Participatory Research approach to examine U.S. Latina/o parents’ perceptions of the need for interventions to prevent childhood disruptive behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 73 publications
4
21
0
Order By: Relevance
“…Overcoming this barrier would necessitate mechanisms to reach parents early in the help seeking process, so that when an invitation is presented, parents are able to understand the meaningfulness of it. One such mechanism may be the community based participatory research model (Niec et al 2014), which would bring parents into the development of programs and stimulate a dialog within target communities, as well as teaching interventionists about the needs of the community. Our approach did reflect this model, including preliminary surveys to identify parent preferences for services, but perhaps more intensive approaches, such as focus groups, would increase buy-in from parents.…”
Section: Potential Barriers To Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Overcoming this barrier would necessitate mechanisms to reach parents early in the help seeking process, so that when an invitation is presented, parents are able to understand the meaningfulness of it. One such mechanism may be the community based participatory research model (Niec et al 2014), which would bring parents into the development of programs and stimulate a dialog within target communities, as well as teaching interventionists about the needs of the community. Our approach did reflect this model, including preliminary surveys to identify parent preferences for services, but perhaps more intensive approaches, such as focus groups, would increase buy-in from parents.…”
Section: Potential Barriers To Engagementmentioning
confidence: 99%
“…Another research group achieved rates of 35 % overall for enrollment in a parent program focused on externalizing problems in a low-income community (Garvey et al 2006), but only 67 % of those who enrolled (23 % of targeted families) attended sessions. Research has also found engagement challenges within minority ethnicity and immigrant groups (Alvidrez 1999;Bjørknes et al 2011;Niec et al 2014), thought to be related to variations in mental health attitudes and help-seeking behaviors. Specific to anxiety, ethnic minority families have been shown to be more likely to drop out of treatment (Kendall and Sugarman 1997).…”
Section: Introductionmentioning
confidence: 96%
“…It is possible that these natural helpers were already predisposed towards the parenting practices taught in PCIT. For example, they endorsed strongly agreeing with timeout before training occurred, even though past research found that Latina/o parents and natural helpers had concerns about the use of this discipline technique Niec et al, 2014). This may be attributable, in part, to the fact that the agency that employs these natural helpers was developed specifically as a way to provide community-based child maltreatment prevention services.…”
Section: Discussionmentioning
confidence: 76%
“…Parent-Child Interaction Therapy (PCIT; Eyberg & Funderburk, 2011) was selected as the focus of this research because of four key characteristics supporting its appropriateness for adaptation into a prevention program that can be delivered by natural helpers in Latina/o communities (Niec et al, in press). First, PCIT possesses features described by US Latinas/os as desirable aspects of parenting interventions (e.g., emphasis on strengthening parent-child relationships, collaboration between families and interventionists, ability to be simultaneously delivered to multiple family groups; Niec et al, in press).…”
mentioning
confidence: 99%
“…First, PCIT possesses features described by US Latinas/os as desirable aspects of parenting interventions (e.g., emphasis on strengthening parent-child relationships, collaboration between families and interventionists, ability to be simultaneously delivered to multiple family groups; Niec et al, in press). Second, the direct coaching of parents during live interaction with their children that occurs in PCIT is related to increased effectiveness (Kaminski, Valle, Filene, & Boyle, 2008).…”
mentioning
confidence: 99%